2020
DOI: 10.1021/acs.jafc.0c03507
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally Relevant-Level CeO2 NP with Ferrous Amendment Alters Soil Bacterial Community Compositions and Metabolite Profiles in Rice-Planted Soils

Abstract: The environmental risks and benefits associated with the introduction of CeO 2 nanoparticle (NP) in agricultural soil must be carefully assessed. The ferrous ion is rich in rhizosphere soil of rice due to the reduction states underground. The aim of this study was to investigate the effects of environmentally relevant-level CeO 2 NP (25 mg•kg −1 ) in the absence or presence of ferrous (30 mg•kg −1 ) amendment on soil bacterial communities and soil metabolomics in rice-planted soil over 150 days. Results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 56 publications
3
34
0
Order By: Relevance
“…For example, no Nitrospirae associated with soil nitrification was found in NR and LR, and its abundance in vascular plant cover was higher than that in bryophyte cover. Interestingly, although Acidobacteria, Chloroflexi and Planctomycetes were more abundant in GS and SS than in other sites, they are commonly used as oligotrophic bacteria [67,68]. This is consistent with previous studies that oligotrophic bacteria are likely to outcompete copiotrophs in environments, for example, the Leshan Giant Buddha, where microorganisms are exposed to constant environmental stress [67,68].…”
Section: Responses Of Microbial Community Diversity and Richness To T...supporting
confidence: 90%
See 1 more Smart Citation
“…For example, no Nitrospirae associated with soil nitrification was found in NR and LR, and its abundance in vascular plant cover was higher than that in bryophyte cover. Interestingly, although Acidobacteria, Chloroflexi and Planctomycetes were more abundant in GS and SS than in other sites, they are commonly used as oligotrophic bacteria [67,68]. This is consistent with previous studies that oligotrophic bacteria are likely to outcompete copiotrophs in environments, for example, the Leshan Giant Buddha, where microorganisms are exposed to constant environmental stress [67,68].…”
Section: Responses Of Microbial Community Diversity and Richness To T...supporting
confidence: 90%
“…Interestingly, although Acidobacteria, Chloroflexi and Planctomycetes were more abundant in GS and SS than in other sites, they are commonly used as oligotrophic bacteria [67,68]. This is consistent with previous studies that oligotrophic bacteria are likely to outcompete copiotrophs in environments, for example, the Leshan Giant Buddha, where microorganisms are exposed to constant environmental stress [67,68]. Ascomycetes are the basis of lichen formation, which partly explain the higher abundance of Ascomycota in LR.…”
Section: Responses Of Microbial Community Diversity and Richness To T...supporting
confidence: 89%
“…Proteobacteria ranked high in the co‐occurrence network of rhizosphere soil in MCB product treatment plots, and the interaction between Proteobacteria and other bacteria in the rhizosphere bacterial network increased and became more and more complex, indicating that Proteobacteria taxa were important in the microbiota of plots treated with the MCB product. Proteobacteria has been reported to harbour a large group of metabolic enzymes, which have a strong influence on global nitrogen and carbon cycles, as well as soil metabolites due to their great metabolic diversity (Spain et␣al ., 2009; Pan et␣al ., 2020). Prevalent organic substrates, such as amino acids, fatty acids and urea, present in rhizosphere soils were reported to be mainly due to the activity of populations of Proteobacteria (Pan et␣al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Proteobacteria has been reported to harbour a large group of metabolic enzymes, which have a strong influence on global nitrogen and carbon cycles, as well as soil metabolites due to their great metabolic diversity (Spain et␣al ., 2009; Pan et␣al ., 2020). Prevalent organic substrates, such as amino acids, fatty acids and urea, present in rhizosphere soils were reported to be mainly due to the activity of populations of Proteobacteria (Pan et␣al ., 2020). The high level of relative abundance of Proteobacteria observed was directly associated with increased potato tuber yield.…”
Section: Discussionmentioning
confidence: 99%
“…Soil microbes play crucial roles in the energy flow, nutrient cycling, decomposition, biodiversity, and stability of soil ecosystems . Luo et al and Pan et al reported that CeO 2 NPs had an obvious effect on the soil microbial community structure and inhibited soil dehydrogenase activities at a concentration range of 25–1000 mg/kg. Other NPs, such as Ag NPs, Cu-based NPs, , TiO 2 NPs, and ZnO NPs, , also decreased the microbial activity and changed the bacterial community composition.…”
Section: Introductionmentioning
confidence: 99%